2017
DOI: 10.1371/journal.pone.0169643
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brain Thyroid Hormone Levels during Early Post-Hatching Development in Zebra Finch (Taeniopygia guttata)

Abstract: Thyroid hormones are closely linked to the hatching process in precocial birds. Previously, we showed that thyroid hormones in brain had a strong impact on filial imprinting, an early learning behavior in newly hatched chicks; brain 3,5,3′-triiodothyronine (T3) peaks around hatching and imprinting training induces additional T3 release, thus, extending the sensitive period for imprinting and enabling subsequent other learning. On the other hand, blood thyroid hormone levels have been reported to increase gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
3
16
0
Order By: Relevance
“…Plasma T3 values in our control and T3-treated birds (mean ± SD, range: 6.64 ± 2.68, 3.83-15.05 and 9.04 ± 5.27, 2.48-29.02, respectively) where within the range reported for this species in other studies (Eng, Williams & Elliott 2013; Yamaguchi et al . 2017).…”
Section: Supplementary Materialssupporting
confidence: 88%
“…Plasma T3 values in our control and T3-treated birds (mean ± SD, range: 6.64 ± 2.68, 3.83-15.05 and 9.04 ± 5.27, 2.48-29.02, respectively) where within the range reported for this species in other studies (Eng, Williams & Elliott 2013; Yamaguchi et al . 2017).…”
Section: Supplementary Materialssupporting
confidence: 88%
“…A potential explanation for the difference in association between maternal hypothyroxinemia and bipolar disorder in females and males is the possibility of a gonadal—thyroid system interaction, which is supported by animal studies. A study with zebra finches found differences between males and females in their levels of thyroid hormones during gestation, as well as upregulation of these hormones into the brain . Males had higher fT4 levels than females throughout gestation, even though their peak levels at the end of gestation were the same.…”
Section: Discussionmentioning
confidence: 99%
“…Triiodothyronine is necessary for molt regulation and migration processes and has also been shown to decrease incubation time in turtles (McGlashan et al 2017). Triiodothyronine also regulates embryonic growth and differentiation of several tissues associated with the muscular, skeletal, and nervous systems (Yamaguchi et al 2017).…”
Section: Discussionmentioning
confidence: 99%